2005
DOI: 10.1074/jbc.m411429200
|View full text |Cite
|
Sign up to set email alerts
|

Eugenol Causes Melanoma Growth Suppression through Inhibition of E2F1 Transcriptional Activity

Abstract: Metastatic malignant melanoma is an extremely aggressive cancer, with no currently viable therapy. 4-Allyl-2-methoxyphenol (eugenol) was tested for its ability to inhibit proliferation of melanoma cells. Eugenol but not its isomer, isoeugenol (2-methoxy-4-propenylphenol), was found to be a potent inhibitor of melanoma cell proliferation. In a B16 xenograft study, eugenol treatment produced a significant tumor growth delay (p = 0.0057), an almost 40% decrease in tumor size, and a 19% increase in the median time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
157
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(174 citation statements)
references
References 28 publications
9
157
0
8
Order By: Relevance
“…Noteworthy, the inhibition of either E2F1 expression or E2F1 transcriptional activity was also reported to enhance the sensitivity of several cell types to apoptotic stimuli, 36,37 and blocking of E2F1 expression in vivo led to an increase of p53-independent apoptosis in UVB-irradiated mouse epidermis. 38 Puga and colleagues observed a reduced E2F1 expression in livers of AHR-deficient mice, indicating that the AHR is required for basal E2F1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, the inhibition of either E2F1 expression or E2F1 transcriptional activity was also reported to enhance the sensitivity of several cell types to apoptotic stimuli, 36,37 and blocking of E2F1 expression in vivo led to an increase of p53-independent apoptosis in UVB-irradiated mouse epidermis. 38 Puga and colleagues observed a reduced E2F1 expression in livers of AHR-deficient mice, indicating that the AHR is required for basal E2F1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Eugenol (4-allyl-2-methoxyphenol) is a naturally occurring phenolic compound which is used as a food flavor and fragrance agent. It is a major component of clove oil and is also present in the essential oils or extracts of many other plants, including cinnamon, basil, and nutmeg (Ghosh et al, 2005). Eugenol has been reported to inhibit the growth of Escherichia coli, Listeria monocytogenes and Lactobacillus sakei (Blaszyk & Holley, 1998;Gill & Holley, 2004) and also exhibits antifungal activity against wood decay fungi ( Tsair-Bor & Shang-Tzen, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that EU is a phenolic compound that induces apoptosis in human colon cancer cells [16]. The antiproliferative activity of EU against melanoma [17], leukemia [18], gastric [19], skin tumor [20], and prostate cancer [21] cells has been confirmed by many researchers. Structure of phenylprepanoids, eugenol scaffold and its derivatives as anticancer as Fig.…”
Section: Introductionmentioning
confidence: 75%
“…Since the E2F transcription factors provide growth for the continuous proliferation of melanoma cells, these results suggest that EU could be developed as an E2F-targeted agent for melanoma treatment [17]. Examination of the mechanism of the anti-proliferative action of EU in the human malignant melanoma cell line, WM1205Lu, showed that it arrests cells in the S phase of the cell cycle.…”
Section: Anticancer Activity Of Phenylpropanoids Eu Scaffold and Itsmentioning
confidence: 99%